The use of fondaparinux and rituximab for recurrent thrombotic events in antiphospholipid syndrome. (October 2022) - Sayar, Zara; Burke, Shoshana; Mittal, Prabal; Cohen, Hannah
Limited evidence exists to guide the management of recurrent thrombosis occurring despite therapeutic anticoagulation in patients with thrombotic antiphospholipid syndrome (APS). In this case series, fondaparinux, with or without an antiplatelet agent, provided an effective and safe option in three patients with thrombotic APS, all two triple and one single positive for antiphospholipid antibodies, who had recurrent venous and/or arterial thromboembolism. Rituximab was also used in all patients. Recurrent events occurred despite therapeutic anticoagulation, including at high-intensity, with warfarin and subsequent low-molecular-weight heparin. There were no major bleeding events. Adjunctive therapies used for thrombosis included catheter-directed thrombolysis and rituximab.